Customer Preference Shift: A Laundry Shop Experience - Narsico, Lalaine O.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was an attempt to investigate the dynamics of a phenomenon that happened in a self-service laundry shop. In the beginning, very few customers would patronize it. But little by little more customers began to frequent the shop and most of these were from the locality. The preference shift of customers was interesting. This situation was believed to reveal some findings that could be used in similar businesses. Qualitative was the method and specifically a case study. It made use of observations and informal interviews of two laundry attendants who have been in at least two years in the laundry shop, one maintenance personnel who has been present since the start of the establishment, and over five hundred regular customers. The observations and interviews revolve around the areas of concern at the start of the laundry shop, key characteristics of regular customers, reasons why customers made the preference shift from going with what they used to do towards availing the new service package, and the challenges encountered in the process of service delivery. Conclusions on the four areas of inquiry were; service value realization was slow and this influenced the initiatives that were made; customer satisfaction was dependent on price, service quality, and rapport and subsequently led to referrals; customers realized that it is more convenient to avail of the new service package, and competition served as a reason to improve service delivery; and sustained customer loyalty and organizational citizenship provide an environment for growth.